A network pharmacology study on mechanism of resveratrol in treating preeclampsia via regulation of AGE-RAGE and HIF-1 signalling pathways - Shi, Jiamiao; Wang, Jiahao; Jia, Ning; Sun, Qinru (Frontiers in Endocrinology, 2023)
Background: Pre-eclampsia (PE) is a hypertensive disorder of pregnancy which threatens millions lives of pregnant women and their babies around the world. Without effective medications, there are thousands of maternal and children’s mortalities every year. Resveratrol (RSV), a non-flavonoid polyphenol extracted from multiple plants, has been shown positive effects in treating hypertension, cardiovascular disorders and even PE. This study aimed to explore the pharmacological mechanism of RSV in treating PE by using network pharmacology and bioinformatics. Methods: Using multiple databases, 66 intersecting targets were obtained from the 347 putative targets of RSV and 526 PE-related genes. Then GO analysis and KEGG analysis were conducted to investigate the functions of the intersecting targets. The protein-protein interaction network and targets-pathways network were drawn and analyzed to illustrate the correlation between targets and pathways. Finally, molecular docking was conducted to calculate the binding energy between RSV and core targets. Results: The results showed that the core targets of RSV were IL6, TNF, IL1B, VEGFA, STAT3 and EGFR. And there existed well binding between RSV and IL6, TNF, IL1B, VEGFA, and EGFR. In addition, we found that RSV mainly functioned in the AGE-RAGE and HIF-1 signaling pathways which are associated with the occurrence and development of PE. Conclusion: In conclusion, our findings indicated that RSV has the effects of regulation of angiogenesis and anti-inflammation and can be the candidate medicine in treating PE.